2007
DOI: 10.1021/je700205n
|View full text |Cite
|
Sign up to set email alerts
|

PρT Measurements of Imidazolium-Based Ionic Liquids

Abstract: Experimental density measurements are reported, and the derived thermodynamic properties, such as the isothermal compressibility, the isobaric expansivity, and the thermal pressure coefficient are presented as Supporting Information for several imidazolium-based ionic liquids (ILs), namely, 1-ethyl-3-methyl-imidazolium bis-(trifluoromethylsulfonyl)imide [C 2 mim][NTf 2 ], 1-heptyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide [C 7 mim][NTf 2 ], 1-octyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
302
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 300 publications
(342 citation statements)
references
References 54 publications
(126 reference statements)
36
302
4
Order By: Relevance
“…The relative standard uncertainty 2.2 % was accepted for the mixture properties. Figure 1 -Comparison of the current experimental density values ( )vs. temperaturewith literature valuesfor pure: (a) aniline-( )Vogel et al [39]; ( )Sumer et al [40];( )Katz et al [41];( )Kumar et al [42];( )Almasi et al [43];( )Costello et al [44]; (⌧) MacNeilet al [45]; ( ) Alonso et al [29]; (b)N,N-dimethylaniline -( )Costello et al [44]; ( )Vogel et al [39]; ( ) Oskoei et al [46]; ( ) Saleh et al [47]; ( ) Pandiyan et al [48]; ( )Katz et al [41]; ( )Kumar et al [42];(⌧) Radwanet al [49]; ( ) Kondaiah et al [50]; ( ) MacNeil et al [45]; ( )Zubinand Naved [33];(c) [bmim][OTf] -( )Vercher et al [51];( )Montalbán et al [52];( )Soriano et al [53];( )Tokuda et al [54];( )Gardas et al [55]; ( ) Fredlake et al [56]; (⌧) Klomfar et al [57];( )Shamsipur et al [58];( )Mbondo et al [59]; ( )Batista et a. [60];( )McHale et al [61]; () Arce et al [34];(d) [bmim][NTf2] -( )Hiraga et al [62]; ( )Kanakubo et al [63]; ( ) de Castro et al [64]; ( ) Jacquemin et al [65]; ( ) Widowati et al [66]; ( ) Currás et al [67]; ( ) Azevedo et al …”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…The relative standard uncertainty 2.2 % was accepted for the mixture properties. Figure 1 -Comparison of the current experimental density values ( )vs. temperaturewith literature valuesfor pure: (a) aniline-( )Vogel et al [39]; ( )Sumer et al [40];( )Katz et al [41];( )Kumar et al [42];( )Almasi et al [43];( )Costello et al [44]; (⌧) MacNeilet al [45]; ( ) Alonso et al [29]; (b)N,N-dimethylaniline -( )Costello et al [44]; ( )Vogel et al [39]; ( ) Oskoei et al [46]; ( ) Saleh et al [47]; ( ) Pandiyan et al [48]; ( )Katz et al [41]; ( )Kumar et al [42];(⌧) Radwanet al [49]; ( ) Kondaiah et al [50]; ( ) MacNeil et al [45]; ( )Zubinand Naved [33];(c) [bmim][OTf] -( )Vercher et al [51];( )Montalbán et al [52];( )Soriano et al [53];( )Tokuda et al [54];( )Gardas et al [55]; ( ) Fredlake et al [56]; (⌧) Klomfar et al [57];( )Shamsipur et al [58];( )Mbondo et al [59]; ( )Batista et a. [60];( )McHale et al [61]; () Arce et al [34];(d) [bmim][NTf2] -( )Hiraga et al [62]; ( )Kanakubo et al [63]; ( ) de Castro et al [64]; ( ) Jacquemin et al [65]; ( ) Widowati et al [66]; ( ) Currás et al [67]; ( ) Azevedo et al …”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…While the correlation cannot distinguish which reference density might be correct, the lines associated with the calculations suggest that the compression data of Gardas, et al (Gardas et al 2007) may be more reliable at lower temperatures, though they are between the slopes from the data at higher T.…”
Section: Pure Component and Solution Densitiesmentioning
confidence: 89%
“…It has been shown that models for DCFIs can lead to successful models for solution properties ( Gardas et al 2007) and ( ) from Jacquemin, et al (Jacquemin et al 2007). Calculations of p using Equation 9.6 with p 0 , 0 and from Jacquemin, et al (Jacquemin et al 2007) ( ) and from Gardas, et al (Gardas et al 2007 Symbols for data of Simnick, et al, (Simnick et al 1979a) ( regression of temperature dependence of Henry's Constant in Equation 9.26, (---) prediction using Equation 9.34 with Henry's Constant for methane in quinoline fitted to data of of Simnick, et al (Simnick et al 1979b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations